Delayed orthodontic care and its association with depression among Chinese adolescents: a cross-sectional study - Li, Yang; Yang, Mengshan; Guo, Botang; Yang, Lusi; Xiaotian, Cui; Zhou, Jiaxing; Wang, Kun; Wang, Shouli; Tang, Ping; Dong, Shitao (Frontiers in Psychiatry, 2025)
ObjectiveAdolescents undergoing orthodontic treatment often face psychological challenges, and delays in treatment may exacerbate these issues. This study explores the prevalence of depressive symptoms among Chinese adolescents receiving orthodontic care and examines the potential link between treatment delays and depressive symptoms.MethodsA cross-sectional study was conducted among adolescent orthodontic patients in Chengde, Hebei Province. Data on demographic factors, treatment delays, and depressive symptoms were collected through structured questionnaires. The Beck Depression Inventory for Youth (BDI-Y) was used to assess depressive symptoms. Logistic regression analysis was performed to evaluate the association between delayed treatment and the risk of depressive symptoms.ResultsThe study found that 32% of adolescent orthodontic patients exhibited depressive symptoms, a rate notably higher than the general adolescent population. Furthermore, 82% of the patients experienced treatment delays. Factors such as age, gender, family income, parental marital status, treatment type, and malocclusion severity (IOTN score) were significantly associated with depressive symptoms. Logistic regression showed that delays of 181–360 days (OR=4.26, 95%CI: 1.37–13.28) and over 360 days (OR=3.40, 95%CI: 1.02–11.37) were significantly associated with a higher risk of depressive symptoms.ConclusionAdolescents undergoing orthodontic treatment are at a heightened risk of developing depressive symptoms, particularly when facing significant treatment delays. Early intervention, including psychological support, education on treatment importance, and financial assistance, is essential to mitigate these risks and improve both oral and mental health outcomes.